Clinics in Diagnostic Imaging (88) - Muttarak M. (2014)
An 83-year old man presented with a painless lump in his left breast for one year. Mammograms showed an ill-defined uncalcified high-density subareolar mass in the left breast and minimal fibroglandular density radiating beneath the nipple into the fatty tissue of the right breast. US showed an irregular, heterogeneously-hypoechoic mass with mild posterior transmission. The differential diagnosis of breast enlargement in men is discussed. Mammographical and US features of gynaecomastia and male breast carcinoma are presented.